Geophysical signatures of New Zealand epithermal Au-Ag deposits, and methods for new exploration. Issue 4 (2nd October 2019) - Kellett, Richard L.; Bromley, Chris J.
ABSTRACT: Volcanic-hosted epithermal Au-Ag quartz vein deposits in the Hauraki Goldfield are investigated using a range of geophysical methods. Tools such as airborne magnetics and ground-based resistivity have focussed on mapping alteration zones, lateral contacts in the volcanic rocks, and prospect scale faults. Reviewing the merits of each geophysical method is valuable as it provides exploration teams with the background material required to apply the most effective tools. The review compiles existing data and summarises the rock properties useful for constraining geophysical models. The Golden Cross mine in the Waitekauri Valley is used to illustrate the strengths and limitations of various techniques. Electrical resistivity is the most valuable rock property to target exploration, but magnetic surveying and gamma-ray spectrometry can reduce the ambiguity between quartz-rich mineralised zones and un-altered volcanic host formations. Density and porosity variations caused by alteration can be mapped with gravity data provided the regional field is defined.